2019
DOI: 10.1016/j.ijheatfluidflow.2019.108426
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the turbulent wake past real seabed elements for velocity variations characterization in the water column.

Abstract: Experimental investigation of the turbulent wake past real seabed elements for velocity variations characterization in the water column.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…From x * > 10, this TKE plateau does not rise and remains at similar z positions, z * ≈ 2. This differs from previous investigations regarding the wake of an isolated cylinder [36] where the TKE maximum rises along the x direction.…”
Section: Mean Flow Characterizationcontrasting
confidence: 99%
“…From x * > 10, this TKE plateau does not rise and remains at similar z positions, z * ≈ 2. This differs from previous investigations regarding the wake of an isolated cylinder [36] where the TKE maximum rises along the x direction.…”
Section: Mean Flow Characterizationcontrasting
confidence: 99%
“…The flow conditions of this experimental study are particular because the turbulence is mainly generated by a wall-mounted cylinder, located upstream of the turbine. Indeed, Ikhennicheu et al [23] pointed out the presence of coherent and energetic flow structures rising up from the cylinder to the surface. On figure 13a, we compare the cross-correlation between the turbine thrust and the streamwise velocity measured at two different locations: about 5 cm (with PIV) and 2 diameters (with LDV) upstream from the turbine.…”
Section: Discussionmentioning
confidence: 99%
“…Ikhennicheu et al [23] present a case study comparison of various elementary obstacles used to reproduce bathymetry variations, like those encountered in the Alderney Race (middle of the English Channel), as shown by its geological description by Furgerot et al [24]. They concluded that wide obstacles (6 times wider than its height) produces the most energetic wake that extends up to the free surface.…”
Section: Introductionmentioning
confidence: 99%
“…As there is no obstacle upstream of the cylinder, the upstream flow is a simple boundary layer developing over the tank floor. Hence the experimental cylinder represents a bump considerably higher than its neighbours, producing some coherent flow structures as it could be encountered in the Alderney Race for instance [4]. For a cylinder height H = 0.25 m, this element represents a key bathymetric element in the area of interest, at a 1 : 20 scale.…”
Section: Experimental Set-up and Measurementsmentioning
confidence: 99%
“…Ikhennicheu et al [15] studied the wake of various elementary obstacles used to experimentally reproduce bathymetry variations, like those encountered in the Alderney Race in the middle of the English Channel. Such bathymetry variations have been observed in-situ, according to the geological description of this particular place presented by Furgerot et al [7].…”
Section: Introductionmentioning
confidence: 99%